Responsabilidade ambiental: uma perspectiva ética para aplicação em políticas públicas - Bilhalva, Margareth Michels (Universidade do Vale do Rio dos Sinos, 2011)
The objective of this research is to work as the issue of environmental liability, seen from an ethical perspective, can influence public policy. To this end, the work develops in articulated parts, from the theoretical analysis of what is meant by ethical perspective, taking as a paradigm the contribution of Hans JONAS, to the repercussions of this perspective in the context of the Democratic State Environmental Law. In the first part, the theory of environmental civil liability was first worked like a particular theory that has its focus on the application of defined public policy behavior. Along these lines, the core of environmental responsibility is no longer the damage, but the very conduct defined in laws, public policies that coagulate. In this new scenario, in post modernity, technology has a fundamental importance, because through it one can control and management of measures to be adopted. Structurally, the theory of environmental liability is based on the axiom that humanity wants a future, that can be analyzed according to two theoretical structural pillars are the "futurology comparative" and "heuristics of fear". The second part is shown the evolution of liability throughout history, which implies the recognition that the identification of the damage as its core is no longer effective for the purposes of the Democratic State Environmental Law. There is, therefore, by imputing causal forecasts established by objective (comparative futurology), qualified by the heuristics of fear, the possibility of controlling the purposes of the state in public policy and the state's obligation to comply with and to adopt concrete measures to implement such policies. It demonstrated the evolution of international environmental liability and its impact on national public policies toward preventive measures. The quest for environmental sustainability, conditioned by its tripod (economic, social and environmental) is also binding public policy. In the third part, work is anthropocentric ethics, contrasting it with the biocentric ethic and its variables. Thus, ethics is anthropocentric enlarged so that the environment is considered. This new perspective permeates the Federal Constitution and has, consequently, changing the conformation of state to a Democratic State of Environmental Law. Public policies, therefore, have provided their conduct, tied at the end of the state. The government, therefore, must take positive actions to implement such plans, otherwise the execution will be required primarily to others, because of the need to be assured an intergenerational responsibility, which ensures a balanced environment and essential to a healthy quality of life.
Keywords: Responsabilidade ambiental; Políticas públicas; Hans Jonas; Ética antropocentrista; Sustentabilidade; Equidade intergeracional; Estado Democrático de direito ambiental; Direito ambiental; Environmental responsibility; Anthropocentric ethics; Sustainability; Intergenerational equity; Democratic State of environmental law; Environmental law; Públic policy; ACCNPQ::Ciências Sociais Aplicadas::Direito